Latest advances in parallel, distributed, and network‐based processing. (11th February 2020) - Merelli, Ivan; Liò, Pietro; Kotenko, Igor; D'Agostino, Daniele
Abstract: This editorial introduces the articles selected for the special issue concerning the International Conferences on Parallel, Distributed, and Network‐Based Processing, which provided insights related to the efficient exploitation of parallel and distributed architectures, including power‐aware computing, application scheduling, and application development for GPUs.